KAJIAN YURIDIS TERHADAP PERATURAN HUKUM DALAM ASPEK TRANSPARANSI TERHADAP RISIKO PADA LAYANAN PRIORITY BANKING - Harsanto, Renny Utaminingsih (Veritas et Justitia, 2020)
One of the new and innovative products offered in context of priority banking services is investment products. This research shall have a look at the transparency aspect of the risk management of this particular bank product offered to priority customers and will be conducted by a juridical normative method. In addition, the author also interviewed a number of key informants working in the banking industry at Bandung.  The legal analysis conducted shows that while quite a number of rules and regulation in regard to risk management of bank investment products exist and are put in place, what it lacks, in terms of customer protection, is transparency.